Pengaruh Kualitas Pelayanan, Partisipasi Anggota Dan Motivasi Berkoperasi Terhadap Sisa Hasil Usaha Anggota - Nur Amilatus Saadah; Rusdarti Rusdarti (Universitas Negeri Semarang, 2023)
This research aims to describe service quality, member’s participation, cooperative motivation to member’s surplus of Koperasi Gema Sejahtera Tembalang Semarang, to analyze the influence of service quality, member’s participation and cooperative motivation to member’s surplus of Koperasi Gema Sejahtera 2018 both simultaneously and partially. The population in this study were all members of Koperasi Gema Sejahtera Tembalang Semarang as many as 214 people. The sample used in this study were 68 people chosen by proportional random sampling technique. Methods of data collection used were questionnaires. Then the data was analyzed using descriptions and multiple regression analysis using SPSS 21 program. The result showed that the service quality belong to fine category, the member’s participation belong to high category, cooperative motivation belong to high category, and member’s surplus belong to fine category with Y regression equation = 1,044 + 0,254 X1+ 0,230 X2+ 0,201X3 . The amount of the influence of service quality, member’s participation and cooperative motivation to the member’s surplus simultaneously was 34,5%, the remaining 65,5% was influenced by other variables not examined in this study, while partially, the influence of service quality was 13,62%, the member’s participation was 7,78%, and cooperative motivation was 6,66% to the member’s surplus of Koperasi Gema Sejahtera Tembalang Semarang.